Incomplete preferences in choice experiments: A note on avoidable noise and bias in welfare estimates - Mitesh Kataria; Jason F. Shogren (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
How does a choice experiment (CE) model derived under standard preference axioms perform for respondents with incomplete preferences? Using simulated data, we show how such miss-specification results in unnecessary noise and bias in welfare estimates, and can be avoided.
Keywords: D61; Q51; 330; Choice experiment; Ordered Logit; Bias; Preference Axioms; Präferenztheorie; Test; Bias; Logit-Modell; Wohlfahrtseffekt